Viabilitas mikroba selulolitik pada media pod dan pulp kakao (Theobroma cacao L.) - Nisfatin Shofiana; Titi Candra Sunarti; Anja Meryandini (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
Cocoa production in Indonesia is increasing from year to year. Cocoa production increased has an impact on increasing waste cocoa pod and pulp. Cocoa pod contains lignocellulose, while cocoa pulp contains many sugars. The composition of cocoa pod and pulp allows the cellulolytic microbe to grow. This study aims to perform microbial selection from fermented cocoa and sugar cane can grow in cocoa pod and pulp (Theobroma cacao). The selection method using the CMC 1%, pod 1%, pulp 1%, and pod 0,5%+pulp 0,5% media. Then, the analysis of reducing sugar using DNS method, while the total sugar analysis using phenol-H2SO4 method. Sugars of hydrolisis result were analyzed quantitatively using TLC. The results of microbial selection on CMC 1%, pod %, pulp 1%, and pod 0,5%+pulp 0,5% media obtained TBT 3.2 have the largest cellulolytic index on the pod 1% media. Isolates TBT 3.2 grown on pod 1% medium produce reducing sugar is 4,965 mg/mL at 30 hours sampling with highest total sugar at 6 hours sampling is 9,789 mg/mL. The types of sugars identified using the TLC are mannose, galactose, glucose, and selobiose.